Make it Mati: The Marketing Mix Strategies and Customer Satisfaction of Resorts Amidst Covid-19 Pandemic - Olivar, Kiven G.; Demain, Christian Dale; Quitoy, Hermy L.; Palmes, Dexter (Archives of Business Research, 2022)
The study intends to assess the level of marketing mix strategies (people, product, place, physical evidence, price, promotion, and process) and the level of customer satisfaction of resorts in Mati. This study also aimed to look into the utilization and importance of the marketing mix strategies and their effectiveness in customer satisfaction. A non-exploratory plan was utilized for the study using elucidating overview strategy procedure. This study used an online survey through google forms to disseminate the survey questionnaire to the 500 beachgoers who visited the resorts of Mati City, Philippines. The study's findings revealed an overall mean score of 3.91 with a standard deviation of 0.560. This means that the marketing mix strategies of resorts in Mati City are high. On the other hand, the customer satisfaction of resorts in Mati has an overall mean score of 4.30 with a standard deviation of 0.649, which is very high. This means that both marketing mix strategies and customer satisfaction are completely correlated and have a significant relationship. The results above have marketing implications for resort management. Sustaining satisfaction among resort customers means that they could provide the need and wants for a beach experience and stay in the aspects. This will like the result in sustainable resort management if they continue to meet the customers' expectations (marketing) and experience (product & service mix).